PSEUDO: uma análise sociocognitiva sobre insinceridades, mentiras e crimes de fraude - Oliveira, Flaubert Mesquita de (2013)
The objective of this work is to analyze the phenomenon of lying, highlighting some uses and social consequences. Lies are a ubiquitous phenomenon, and in many cases they even promote social harmony. Furthermore, telling lies is an expression of individuality: it is the expression of relative autonomy that the subject has towards their social environment allowing them to defend their most personal interests. The work also aims to examine the concept of habitus applied to the social production of lies. Thus, the liars produce their lies aiming to obtain certain effects on their audiences. There are certain social cognitive principles that structure the kind of lie that is usually told to the public. Finally, the perpetrators of crimes of fraud and other deceptive practices may suffer a criminal prosecution because the damage they cause affects important social values recognized by the state, and are not restricted to the victim‟s chagrin. In the most common forms of fraud, the crooks make tempting offers to victims exploiting some of their standardized behaviors and reactions. To understand the fragility of the victims to scams is an attempt to understand how a social phenomenon as usual as is the lie can still surprise and cause perplexity